Compressive Strength of Brick Containing Crushed Cockle Shell as Partial Sand Replacement - Muhammad Nazrin Akmal, Ahmad Zawawi; Khairunisa, Muthusamy; Shahrul Munir, Abdul Nasir; Mohamad Firdaus, Mohamad Azhar; Aizam, Uzer (Universiti Malaysia Pahang, 2016)
Negative impact to the environment posed by increase in the river sand mining and dumping of cockle shell waste by cockle processing factory has led to the development of brick containing this waste material. The present research investigates the strength performance of cement sand brick containing crushed cockle shell as partial sand replacement. At the first stage of the experimental work, mixes containing various percentage of crushed cockle shell as partial sand replacement were prepared in form of cubes and then water cured. Based on the compressive strength test conducted, only the best performing mix containing cockle shell were used to produce brick for the second stage of the work. The bricks were subjected to water curing until the testing age. The compressive strength test was carried out at 7 and 28 days. The findings show that the compressive strength of the mix increases when suitable content of crushed cockle shell is used. Addition of suitable content of crushed cockle shell up to 20% successfully enhances the compressive strength of the mortar mix. Crushed cockle shell brick exhibit better strength performance compared to control specimen throughout the curing age. Success in combining waste from fisheries industry in brick making able to reduce the use of natural river sand and decrease amount of cockle shell disposed at dumping site.